Ingestion of microplastics by commercial fish off the Portuguese coast. Issue 1 (15th December 2015) - Neves, Diogo; Sobral, Paula; Ferreira, Joana Lia; Pereira, Tânia
Abstract: The digestive tract contents of 263 individuals from 26 species of commercial fish were examined for microplastics. These were found in 17 species, corresponding to 19.8% of the fish of which 32.7% had ingested more than one microplastic. Of all the fish that ingested microplastics, 63.5% was benthic and 36.5% pelagic species. A total of 73 microplastics were recorded, 48 (65.8%) being fibres and 25 (34.2%) being fragments. Polymers were polypropylene, polyethylene, alkyd resin, rayon, polyester, nylon and acrylic. The mean of ingested microplastics was 0.27 ± 0.63 per fish, (n = 263). Pelagic fish ingested more particles and benthic fish ingested more fibres, but no significant differences were found. Fish with the highest number of microplastics were from the mouth of the Tagus river. Scomber japonicus registered the highest mean of ingested microplastics, suggesting its potential as indicator species to monitor and investigate trends in ingested litter, in the MSFD marine regions. Highlights: Microplastics were found in 19.8% of the 263 fish from 26 species; 65.8 % were fibres and the remaining 34.2% particles. Plastic polymers were polypropylene, polyethylene, alkyd resin, rayon, polyester, nylon and acrylic Pelagic species ingested more particles, benthic species ingested more fibres and 32.7% of the fish had more than one microplastic Scomber japonicus, registered the highest value of ingested microplastics Fish from trawls near the Lisbon metropolitan area and the Tagus river estuary had the highest mean of ingested microplastics